Effect of electroless nickel-boron (EN-B) surface finish on solderability of SAC305 and solder joint strength - Hardinnawirda, Kahar (2017)
Rapid developments in technology have been a great challenge for the electronics industry to keep up with the industrial requirement to provide cost-effective smart devices while, at the same time, maintaining their quality. The quality of electronic packaging is directly related to the solder joints, which turn out to be the main concern in the electronics industry. In the current study, an attempt was made to study the ability of electroless nickel boron as printed circuit board’s surface finish by study the solderability, investigate the type of intermetallic compound formation and growth after reflow soldering and isothermal aging as well as determine the effect of cooling rate and isothermal aging temperature (125°C and 150°C) on the intermetallic compound formation and solder joint's strength. Electroless nickel boron was deposited on a copper substrate through electroless plating method. Several sodium borohydrade concentration were used, 0.4, 0.6, 0.8, 1.0 and 1.2 g/L. in order to investigate the effect of Boron content on the electroless nickel boron. The morphology of the electroless nickel boron surface finish was analysed by using scanning electron microscopy. The phase structure analysis of the surface finish also analysed using x-ray diffraction and surface roughness measurement was carried out using 3D Roughness Reconstruction software. Then, reflow soldering was conducted using Sn-3.0Ag-0.5Cu solder alloy to form the solder joint prior to cooling process which two different cooling medium was used which is air (for slow cooling rate) and water (for fast cooling rate). The solderability of the surface finishes then evaluated by measuring the contact angle between the Sn-3.0Ag-0.5Cu solder alloy and the electroless nickel boron surface finish. After that, a set of samples were underwent isothermal aging for 250, 500, 1000 and 2000 hours for 125°C and another set for 150°C prior to lap shear test to study the strength of the solder joint. Thickness of the intermetallic compound and surface fractured of the shear test were analysed by using Optical microscope, Scanning Electron Microscopy while Field Emission Scanning Electron Microscope that equipped with energy dispersive x-ray spectroscopy system was used to identify the element on the intermetallic compound. From the results, it was observed that the suitable NaBH4 concentration to be used on printed circuit board to deposit an electroless nickel boron surface layer is 0.6 g/L NaBH4 based on its ability to provide most solderable surface with 42.5° contact angle. After reflow process, it was observed that intermetallic compound consist of of Ni3Sn4 and (Ni, Cu)3Sn4 for both air and water cooling. However, as the joint thermally aged (1000 hours), the intermetallic compound changes to only (Ni, Cu)3Sn4 for both cooling. In term of cooling rate, it was found that slow cooling rate (15.7 ˚C/min) produced higher intermetallic compound thickness for both as reflow and aging compared to fast cooling rate (110.5˚C/min) regardless the aging temperature used. However, 125°C provided thinner intermetallic compound compare to 150°C due to its higher activation energy. Besides, the strength of the solder joint was found to decrease as intermetallic compound thickness increased owing to the cooling rate and 125°C shows stronger joint than 150°C aging temperature. However, the influent is minimal compared to the formation of underfill and spalling behaviour of the intermetallic compound that seems to affect the solder joint strength significantly instead. Nevertheless, electroless nickel boron surface finish shows promising ability to be an alternative in regards to the surface finish on printed circuit board in electronic industry.